(untitled) (Perner’s Contacts, 2011)
The paper deals current level cycleways in Finland and Ostrava. The specific examples show the state of cycleways and the opportunity to solve some of the promlem’s place on finnish cycleways. Further shows tThe paper deals current level cycleways in Finland and Ostrava. The specific examples show the state of cycleways and the opportunity to solve some of the promlem’s place on finnish cycleways. Further shows to some dangerous places on Ostrava’s cycleways.o some dangerous places on Ostrava’s cycleways.The paper deals current level cycleways in Finland and Ostrava. The specific examples show the state of cycleways and the opportunity to solve some of the promlem’s place on finnish cycleways. Further shows to some dangerous places on Ostrava’s cycleways.